MARKETING OF LOCAL BRANDS: HOW SUPPORTING NATIONAL PRODUCTION BUILDS TRUST - Graf-Gudz, Svetlana (Global Prosperity, 2025)
The article focuses on the analysis of marketing strategies employed by local brands in the context of supporting national production and building consumer trust. The aim of the study is to identify the factors that contribute to the development of local brands in the furniture industry, with particular attention given to the influence of governmental and municipal initiatives on marketing strategy. Methodology and methods: the study applied general scientific methods of cognition, including analysis and synthesis, induction and deduction, a systems approach, comparative analysis, modeling, and generalization. The research findings demonstrate that the marketing of local brands is based on an integrated application of key management theories – namely, the resource-based view of the firm, the marketing mix theory, and institutional theory. All of these approaches emphasize innovation, digitalization of processes, environmental orientation, and the integration of circular economy principles. These processes are especially prominent in the furniture sector, where the adaptation of products to market challenges through sustainability and digital solutions becomes a prerequisite for creating a sustainable competitive advantage. The study shows that these theoretical foundations support the development of a strategic vision for local brands as responsible market players. It was found that the strategic growth of local brands is unattainable without a focus on social responsibility and sustainability, which are increasingly seen not as optional but as societal expectations. The research illustrates that a brand’s active involvement in community life, support for local initiatives, and contributions to territorial development foster an emotional connection with consumers, grounded in consumer ethnocentrism. This generates added value for the brand, which begins to be associated not only with the product itself but also with identity, community, and national values. The role of the state as a strategic partner was also examined, highlighting its provision of essential infrastructural, financial, and regulatory support. Mechanisms such as subsidies, the development of local governance, environmental initiatives, and the simplification of bureaucratic procedures are shown to be critical in ensuring the sustainable development of local producers, particularly in the context of global competition. The practical significance of the study lies in substantiating effective approaches to the strategic development of local brands as components of economic stability and social integration.